Road to Bali - Walker, Hal, 1896-1972; Hope, Bob, 1903-2003; Crosby, Bing, 1903-1977; Lamour, Dorothy, 1914-1996 (Los Angeles, CA : Delta Entertainment, 2003)
Two vaudeville actors flee from marriage-minded women to the island of Bali, where they help a beautiful princess out of trouble.
Features: "The road to Hollywood" a fictional biography of Bing Crosby's rise to fame.
Bob Hope, Bing Crosby, Dorothy Lamour, Murvyn Vye, Peter Coe.
MPAA rating: Not rated.
DVD, Dolby digital mono.
Keywords: Man-woman relationships -- Drama; British Association of Landscape Industries -- Drama; Feature films; Road films; Comedy films